STATISTICAL ANALYSIS OF BUSINESS RISKS IN UKRAINE UNDER THE CONDITIONS OF MARITAL STATE AND WAYS TO OVERCOME THEM - GONTAREVA, Irina; KOVALOVA, Viktoriia; MYKYSHA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the main risks faced by business entities in Ukraine with a full-scale Russian invasion of Ukraine in 2022. The modern dynamics of registration of new business entities since the beginning of the full-scale war for March - August 2022 were analyzed. The main problems that made it difficult to do business in Ukraine since the beginning of the full-scale invasion were identified, namely consumer insolvency, a drop in demand for the products of enterprises, and a lack of funding. , destruction of supply chains, long-term power outages due to military attacks on energy facilities, rising costs of raw materials, materials and energy resources, and a shortage of skilled workers. The article also analyzed the rating of doing business in strategic cities of Ukraine, namely Lviv, Odesa, Kharkiv and Dnipro. Preventive measures were also proposed to reduce business risks in Ukraine under martial law.Among the main recommendations: analysis of the insurance policy and the possibility of asset protection; development of crisis management and evacuation plans; strengthening relations with other companies and authorities to provide support in crisis; analysis of risks in the market and adaptation of production in accordance with changes in demand; development of different planning and budgeting scenarios for different market conditions; diversification of supply chains and search for alternative sources of raw materials; monitoring of financial markets and timely response to changes; development of a strategy to reduce currency risks and other financial losses; development of alternative sources of financing and investments; developing an emergency plan and having alternative suppliers of raw materials; ensuring the stability of infrastructure and transport links; monitoring of global events and geopolitical risks to predict possible supply interruptions; development of emergency power plans and backup solutions - to ensure power supply in case of energy shortage; reducing dependence on centralized energy sources and developing alternative energy sources, etc.